Music Creation Based on Folklore - Palumun Peterus Ginting (Budapest International Research and Critics University, 2019)
This paper discusses the model of music creation compositions that departs from the folklore of Senggulat Mbacang owned by Karoness in North Sumatra. This folklore e is commonly referred to as Turi-turin Culture by Karoness. Selanggulat Mbacang, Turi-turian Culture is very popular among Karoness. This folklore is usually delivered orally and is very musical in nature. Sengulat Mbacang, Turi-turian culture has a slice of mbacang fruit or mango fruit. Senggulat mbacang, Turi-turian has a very strong impression in representing the social reality of the life of Karoness. This is a compelling reason for composers to reinterpret this folklore through the composition of music with the title Senggulat Mbacang. Trying to explore Karo culture, traditional elements and other musical elements, trying to the folklore through musical activities. Presenting and reinterpreting folklore that is usually done orally becomes a whole musical composition without losing the core of the original meaning or meaning of the story.